Optimization of algal turf scrubber (ATS) technology through targeted harvest rate. (February 2020) - Siville, Bert; Boeing, Wiebke J.
Abstract: Algal turf scrubbers (ATSs) may remediate wastewater while growing valuable filamentous macroalgal biomass. We introduce a new method to estimate growth rate on ATS and optimize harvest rate maximizing biomass production. 12 ATS (0.10 × 0.25 m surface area) each grew polycultures at 27 °C, 32 °C, and 45 °C with replete BG11 media. Every three days, we harvested one ATS and dried and weighted algae biomass until all 12 ATS were used. Growth rate was highest at 32 °C with r = 0.32 ± 0.04. To optimize harvest rate at 32 °C, four ATS each were harvested every 7, 14, or 21 days over two months. We found that optimal harvest rate for biomass production was between one to two weeks. Nutrient absorption was not influenced by harvest rate. Increased biomass (potentially also of bacteria) observed on ATS that were harvested less frequently may offset the increased growth rates observed in the more frequent harvest treatments. Graphical abstract: Unlabelled Image Highlights: Algal turf scrubbers (ATSs) can use wastewater to grow easy harvestable benthic alga. Optimizing harvest rate can increase biomass yield. Algae growth rate was highest at 32 °C. 7 to 14-day harvest rate maximized biomass production. Nutrient absorption was not influenced by harvest interval.